A computerised calibration service supporting system. I: System design and development. (29th October 2004) - Liu, Thu-Hua; Trappey, Amy J.C.; King, Ze-Jun
A computerised calibration service supporting system (CCSS) is developed to assist the calibration procedure by easy accessing of the service and customers' databases. The calibration service procedure is modelled using IDEF0 method, which depicts the process flow of the calibration service. Based on the required data types of the process flow, an EXPRESS data model is defined for the system. This data model is used to construct both the application class lattice and object-oriented database schema. The system implementation follows the STEP enabling information system development procedure. The procedure includes process modelling, data modelling, object class building (C++), and programming of the decision support system integrated with the database for instanced object populations. This system takes advantages of calibration data management and decision supports through a web interface, and provides the calibration centre, a computerised tool to serve its customers efficiently and effectively.